Penataan Kawasan Wisata Pantai Batu Cincin Di Kabupaten Ende - Mariam, Siti; Siso, Silvester M.; Dede, Petrus Jhon Alfred Depa (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2022)
One of the beaches that has good natural potential and has been recognized by the Department ofCulture and Tourism of Ende Regency is Stone Ring Beach which is located in Ende Regency. StoneRing Beach is located in Raporendu Village, Nangapanda District, Ende Regency. The stone ringbeach itself is a cliff that is at sea level and there are holes like stone rings that are unique on thebeach. There is no road as vehicle access to enter Stone Ring beach because the area is still natural.The research with the title